KETEPATAN PENGGUNAAN ALAT LABORATORIUM DAN UJI FITOKIMIA SEBAGAI INDIKATOR KINERJA DALAM ANALISIS TUMBUHAN LOKAL - Herlena, Riska (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2025)
The accuracy of laboratory equipment use and phytochemical testing determines the validity of local plant analysis, particularly for Baccaurea macrocarpa. This study aimed to evaluate practicum students’ skills in using laboratory equipment and conducting phytochemical tests as performance indicators. A descriptive quantitative design involved 30 participants assessed on nine criteria: digital balance, measuring cylinder, pipette, funnel, timer, alkaloid test, flavonoid test, saponin test, and triterpenoid/steroid test. Each criterion was scored on a 1–5 scale. Results showed an average total score of 34.8, with the following distribution: Accurate 53.33%, Less Accurate 26.67%, and Highly Accurate 20.00%. Students in the “Less Accurate” category struggled with precision tools (digital balance, pipette) and interpretation in phytochemical assays (saponin, triterpenoid/steroid). This study concludes that laboratory skills and phytochemical test accuracy can serve as performance indicators in the analysis of Baccaurea macrocarpa.